An Analysis upon Several Marketing Management Techniques of SMEs in Indian Context: A Sample Survey: Exploring Innovative Marketing Practices and Challenges in Indian SMEs (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Worldwide, the micro small and medium enterprises (MSMEs) have been accepted as the engine of economic growth and for promoting equitable development. The major advantage of the sector is its employment potential at low capital cost. This constitute over 90 of total enterprises in most of the economies and are credited with generating the highest rates of employment growth and account for a major share of industrial production and exports. In India too, the MSMEs play a pivotal role in the overall growth of the industrial economy of the country. Rather, Small and medium Enterprises in India are known as the backbone of the economy. The reason behind is that these enterprises are employing about 40 of India's workforce and contributing 45 to India's manufacturing output, they play a critical role in generating millions of jobs, especially at the low-skill level. The country's 1.3 million SMEs account for 40 of India's total exports. The current scenario clearly states that the growth of our economy is impossible without the growth and development of these enterprises but these enterprises are far behind the large counterparts in the economy.Small and medium enterprises (SMEs) have been the backbone of the Indian economy. The good part first. Employing close to 40 of India's workforce and contributing 45 to India's manufacturing output, SMEs play a critical role in generating millions of jobs, especially at the low-skill level. The country's 1.3 million SMEs account for 40 of India's total exports. The bad thing is that SMEs in India, due poor adoption of technology and marketing practices have led to very poor productivity.Although they employ 40 of India's workforce, they only contribute 17 to the Indian GDP. Now SME’s have realized the importance of various marketing practices as now they are utilizing various marketing tools like internet platform, digital advertising in metro cities, mobile applications for customers, CRM and many more The study aims to know various innovative marketing practices at SMEs, trends, challenges and other related issues.